The Orchid Bee Communities in different phytophysiognomies in the Atlantic Forest: from lowland to montane rainforests - Willian Moura Aguiar; Renata Lee dos Santos Medeiros; Candida Maria Lima Aguiar; Isaura Gabriela Mendonça Borges (Sociobiology, 2017)
To investigate species composition, diversity, richness, and monthly abundance of orchid bees in different types of dense rainforest, placed in different altitudes, the orchid bees were collected for 11 months in three vegetation types: dense montane ombrophilous forest (DMOF), dense submontane ombrophilous forest (DSOF, with two sites points), and dense lowland ombrophilous forest (DLOF). Were collected 1,945 males of 20 species using aromatic traps. The DMOF showed the highest species richness (19), and diversity (H’ = 2.42) , whereas the DSOF_1 showed the highest abundance (775). Euglossa cordata (Linnaeus) was the most abundant species in three areas, and Euglossa ignita Smith was the most abundant species in the DSOF_2 . Abiotic factors were correlated with some community parameters. Our study reveals the importance of preserving different phytophysiognomies within the same biome to conserve orchid bees.